2021
DOI: 10.1002/celc.202100335
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Reasons for the Variable Efficiencies of Organic Electrocatalysts Used for Converting Carbon Dioxide to Methanol

Abstract: Pyridinium (the protonated form of pyridine) and related compounds have been proposed to be promising homogenous electrocatalysts in the electrochemical reduction of CO 2 to methanol due to the low overpotential required to achieve faradaic yields of about 20 %, although the percentage yields vary dramatically between different research groups. In this study, experimental conditions were varied during the electrolysis of CO 2 at a platinum electrode in the presence of pyridinium to determine the reasons for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…Interestingly, this decline in peak intensity after 3 h of reaction implied a second electrochemical reaction involved reduction of this initial product. It should be noted that when products were left in the reactor cell and subjected to low potentials, more highly reduced products may result; 44 earlier studies showed situations where products were seemingly lost from the reaction solution, and this was exacerbated by performing the reactions at low concentrations 45 . Moreover, different potentials resulted in various products (Fig.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this decline in peak intensity after 3 h of reaction implied a second electrochemical reaction involved reduction of this initial product. It should be noted that when products were left in the reactor cell and subjected to low potentials, more highly reduced products may result; 44 earlier studies showed situations where products were seemingly lost from the reaction solution, and this was exacerbated by performing the reactions at low concentrations 45 . Moreover, different potentials resulted in various products (Fig.…”
Section: mentioning
confidence: 99%
“…Based on the products identified by NMR, we can propose a reduction mechanism that results in formic acid as the main product. This mechanism is based on multiple recent publications describing the use of a similar copper-based catalyst and formation of similar products 20,44,45 . A plausible mechanism for the HKUST-1/C composite is shown in Fig.…”
Section: mentioning
confidence: 99%
“…35 Moreover, different potentials result in various products (Figure S11). [35] The faradaic e ciency of formic acid and hydrogen gas produced with different potentials is displayed in Figure S11. The formation of formic acid at lower potential is higher and reduces with an increase in potential because of the hydrogen evolution reaction (Figure S11).…”
Section: Sample #mentioning
confidence: 99%
“…It should be noted that when products are left in the reactor cell subjected to low potentials, further reduced products may result, 34 and studies have identi ed situations where products may be seemingly lost from the reaction solutions, exacerbated by the reactions being carried out at low concentrations. 35 Moreover, different potentials result in various products (Figure S11). [35] The faradaic e ciency of formic acid and hydrogen gas produced with different potentials is displayed in Figure S11.…”
Section: Sample #mentioning
confidence: 99%